Analisis Faktor-Faktor yang Mempengaruhi Kecurangan di Perguruan Tinggi Swasta di Indonesia - Diah Astuti; Arief Rahman (AKUA: Jurnal Akuntansi dan Keuangan, 2025)
Fraud in higher education institutions, particularly in Private Universities (Perguruan Tinggi Swasta/PTS), poses a serious threat to institutional reputation, financial integrity, and governance effectiveness. Such unethical practices can undermine public trust and disrupt the sustainability of educational operations. This study aims to analyze the factors influencing fraud in Indonesian PTS by employing the Institutional Theory framework, which emphasizes how organizational behavior is shaped by institutional pressures. Specifically, this research examines the influence of coercive, mimetic, and normative pressures, as well as the role of information technology in fraud prevention efforts. A quantitative approach using a survey method was applied, involving 100 respondents consisting of structural lecturers and administrative staff across various PTS in Indonesia. The collected data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the proposed hypotheses. The results indicate that coercive, mimetic, and normative pressures significantly affect fraud occurrence, suggesting that institutional environments strongly shape behavioral tendencies. Additionally, the effective utilization of information technology was found to play a crucial role in strengthening internal controls and reducing opportunities for fraudulent practices. This study contributes theoretically to the development of financial governance research in the education sector by integrating institutional theory with technological perspectives, and it offers practical insights for university management in formulating more effective, measurable, and sustainable anti-fraud policies to safeguard institutional accountability and credibility.